Synergisms in Science: Climate Change and Integrated Pest Management Through the Lens of Communication—2019 Student Debates. Issue 5 (29th October 2020) - Holt, Jocelyn R; Bernaola, Lina; Britt, Kadie E; McCullough, Chirs; Roth, Morgan; Wagner, Jennie; Ragozzino, Max; Aviles, Leslie; Li, Zhilin; Huval, Forest; Pandey, Manoj; Lee, Benjamin W; et al.
Abstract: Every year, the Student Debates Subcommittee (SDS) of the Student Affairs Committee (SAC) for the annual Entomological Society of America (ESA) meeting organizes the Student Debates. This year, the SAC selected topics based on their synergistic effect or ability to ignite exponential positive change when addressed as a whole. For the 2019 Student Debates, the SAC SDS identified these topic areas for teams to debate and unbiased introduction speakers to address: 1) how to better communicate science to engage the public, particularly in the area of integrated pest management (IPM), 2) the influential impacts of climate change on agriculturally and medically relevant insect pests, and 3) sustainable agriculture techniques that promote the use of IPM to promote food security. Three unbiased introduction speakers gave a foundation for our audience to understand each debate topic, while each of six debate teams provided a strong case to support their stance or perspective on a topic. Debate teams submitted for a competitive spot for the annual ESA Student Debates and trained for the better part of a year to showcase their talents in presenting logical arguments for a particular topic. Both the debate teams and unbiased introduction speakers provided their insight toward a better understanding of the complexities of each topic and established a foundation to delve further into the topics of science advocacy and communication, climate change, and the many facets of integrated pest management.